Does age play a role in fever and neutropenia events and complications: A comparison of adolescents versus younger children with cancer at a tertiary care pediatric hospital, a pilot project. Issue 4 (9th December 2022) - Kirolos, Nardin; Tang, Ken; Abbott, Lesleigh S.
Abstract: Background: Adolescents and young adults with cancer (AYA) are a complex group of patients. The development of fever and neutropenia (FN) is a potentially lethal complication of chemotherapy. Risk stratification of patients with FN has become increasingly valuable allowing for early intervention and to guide treatment type and duration appropriately. There are risk stratification guidelines that exist, but most are validated in young children with cancer (YCWC). AYA are frequently shown to have more numerous and severe side effects from chemotherapy. Aims: This study aimed to identify whether age contributes to the incidence and severity of FN. Methods and Results: Patients diagnosed with a malignancy in a 5‐year period at our institution were included from ages 0–18 years. We reviewed details of their FN events, including duration of hospital admission, source (bacterial/fungal), PICU admission and duration, positive blood cultures and mortality. Adolescents with cancer (AWC) had a trend of being 1.56 times more likely to have FN events (CI 95% 0.936–2.622, p = 0.087). Assessment of the duration of PICU stay showed that AWC were 4.9 times more likely to have longer admissions (CI 95% 0.998–24.067, p = 0.050). There was no significant difference between the two groups in the rate of PICU admission, positive cultures, identification of a bacterial or fungal source, hospital admission duration or mortality from FN. Conclusion: This study demonstrated a trend towards AWC being more likely to develop FN events. When such events occur in this group, the severity of them may be heightened as evidenced by longer duration of PICU admission.